DEVELOPMENT OF E-LKPD BASED ON LOCAL WISDOM IN CONVENTIONAL BIOTECHNOLOGY SUB-MATERIALS TO TRAIN STUDENT’S CREATIVE THINKING SKILLS - Indriana Restianingrum; Isnawati Isnawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Learning during the COVID-19 pandemic was less effective, especially for topics that required experimental activities such as conventional biotechnology; also, limited learning media was used due to the lack of technology. Conventional biotechnology is considered an abstract material, unsuitable if only explained without practice. Conventional biotechnology will be easier to understand if integrated with local wisdom topics. Both topics can be studied together to practice creative thinking skills because Indonesian students are still in the low-medium category. Therefore, the development of digital learning media is needed to overcome these problems. This research aimed to develop an E-LKPD in conventional biotechnology based on local wisdom, which is valid, practical, and effective in training students' creative thinking skills. This study used a 4D model through define, design, and develop stages without the disseminate stage. The researcher collected data through the validation method, observation sheet, the results of E-LKPD completeness, and response questionnaire sheets for 20 students of class XII MIPA 7 SMA Negeri 8 Surabaya. The data obtained were analyzed using descriptive-quantitative technique. The results show very valid E-LKPD with a 3.80 score, which is suitable for learning. Very practical E-LKPD based on the observation sheet with a 97.50% score. Very effective E-LKPD based on the completeness of learning outcomes 83.33%, indicator achievement of 86.88%, and positive responses for E-LKPD of 97.68%. E-LKPD is feasible regarding validity, practicality, and effectiveness in training creative thinking skills. Thus, this research is useful for practicing creative thinking skills and providing digital learning facilities for students. Keywords: E-LKPD, conventional biotechnology, local wisdom, creative thinking skills.